COVID-19 Dermatologic Manifestations: Issues More Than Skin-deep - Elena Pastukhova (University of Ottawa Journal of Medicine, 2023)
Cutaneous manifestations of COVID-19 have become increasingly more reported. These dermatoses can either precede, accompany, or follow respiratory symptoms of COVID-19, and some have also been correlated with COVID-19 severity. Although COVID-19-related skin changes are relatively rare, there is an even greater paucity of such data in skin of colour. While research into the pathophysiology into this phenomenon is in its nascency, it is paramount to recognize the need for diversification, especially considering the racial disparities of COVID-19. The present discussion raises a deeper reflection of teaching and understanding dermatology of skin of colour in the medical profession.